Creatine kinase imaging (CKI) for in vivo whole-brain mapping of creatine kinase reaction kinetics - Mark Widmaier; Antonia Kaiser; Pontus Pandurevic; Song-I Lim; André Döring; Zhiwei Huang; Daniel Wenz; Ying Xiao; Yun Jiang; Yan Lin; Lijing Xin (Proceedings of the National Academy of Sciences, 2025)
The creatine kinase (CK) is a key enzyme involved in brain bioenergetics, playing an important role in brain function and the pathogenesis of neurological and psychiatric diseases and cancers. However, imaging its activity noninvasively in the human brain remains a significant challenge. This study aims to advance 31 P magnetic resonance fingerprinting for Creatine Kinase Imaging (CKI). The method was implemented and validated on a clinical 7 Tesla MRI scanner. CKI enables whole-brain mapping of CK forward rate constant, revealing regional differences. Furthermore, a functional CKI (fCKI) study demonstrated a CK activation map in response to visual stimulation, revealing an increase in CK forward rate constant in the visual cortex. The novel imaging modalities, CKI and fCKI, have the potential to offer insights into brain bioenergetics both at rest and during activity, in both healthy and pathological conditions.